2017
DOI: 10.1038/srep44584
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase-5 inhibition preserves renal hemodynamics and function in mice with diabetic kidney disease by modulating miR-22 and BMP7

Abstract: Diabetic Nephropathy (DN) is the leading cause of end-stage renal disease. Preclinical and experimental studies show that PDE5 inhibitors (PDE5is) exert protective effects in DN improving perivascular inflammation. Using a mouse model of diabetic kidney injury we investigated the protective proprieties of PDE5is on renal hemodynamics and the molecular mechanisms involved. PDE5i treatment prevented the development of DN-related hypertension (P < 0.001), the increase of urine albumin creatinine ratio (P < 0.01),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 52 publications
2
30
0
1
Order By: Relevance
“…In experimental studies, the adaptation of renal RI to facilitate detailed renal injury has been limited, primarily because of technical difficulties in imaging mice versus humans, including the small size of mice, the high heart rates of small animals, and the high speed for data acquisition and storage. However, recently developed imaging techniques allow us to obtain high-frequency and high-resolution images with ultrasound to monitor blood flow and analyze RI values in the tiny vessel [21]. Accordingly, we observed that RI levels were increased in the early stage of HFD-feeding, and they continued to increase with long-term HFD-feeding.…”
Section: Discussionsupporting
confidence: 50%
“…In experimental studies, the adaptation of renal RI to facilitate detailed renal injury has been limited, primarily because of technical difficulties in imaging mice versus humans, including the small size of mice, the high heart rates of small animals, and the high speed for data acquisition and storage. However, recently developed imaging techniques allow us to obtain high-frequency and high-resolution images with ultrasound to monitor blood flow and analyze RI values in the tiny vessel [21]. Accordingly, we observed that RI levels were increased in the early stage of HFD-feeding, and they continued to increase with long-term HFD-feeding.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, miR-22 selected by NGS analysis was also decreased in the UExo of KD compared to that of NR cats. Altered miR-22 expression was reported in several KDs, and it was upregulated in the kidney of diabetic mice ( 29 ) and rhabdomyolysis-induced acute kidney injury (AKI) mice ( 30 ) but downregulated in human renal cell carcinoma ( 31 ). Further, miR-22 regulates the synthesis of collagen IV and α-smooth muscle actin in tubulointerstitial fibrosis by targeting phosphatase and tensin homolog (PTEN) ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of resistivity and pulsatility indexes to the exploration of mechanisms of renal vascular dysfunction in preclinical models has been limited [ 7 , 9 ]. In this study, we utilized a novel non-invasive ultrasound technique to evaluate indices of kidney microvascular health (RRI and PI) in a preclinical model of diabetic nephropathy, as has been previously reported [ 49 ].…”
Section: Discussionmentioning
confidence: 99%